The Potential Activity of Kecombrang (Etlingera elatior) Leaf, Flower, and Stem Extracts on the Duration of Wound Healing in Mice (Mus musculus) - Zunnita, Oktaviana; Moerfiah, .; Apriana, Rinal (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2024)
Wound is skin tissue damage due to trauma from a sharp object.  Kecombrang flower extract is known to be effective in speeding up the healing of wounds because it contains flavonoids, saponins, tannins and steroids. The leaves and stems also contain these compounds, so this research was conducted to see the difference in the potential activity of the wound healing process of the kecombrang plant on the time of wound healing. Natural ingredient extracts are wound healing agents that can fight infection and speed up wound healing. This study used 5 treatment groups consisting of control (-) distilled water, control (+) Povidone Iodine 10 %, leaf extract 10 %, flower extract 10 %, and stem extract 10 %. The parameters observed were the length of the wound and the condition of the wound until the wound healed. The obtained data were analyzed statistically using ANOVA for complately randomized factorial designed. The results of the research show that extracts of kecombrang leaves, flowers, and stems have activity in accelerating the healing process of cut wounds and produce different effects on healing time. Wound healing time for leaf extract is 12 days, flower extract and stem extract is 10 days. The conclusion of this study shows that there is a very real difference in wound healing from treatment with the best treatment for wound healing is the flower extract with highest healing score of 6.42.